If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -4)(x + 9)(x + 13) = 0 Reorder the terms: (-4 + x)(x + 9)(x + 13) = 0 Reorder the terms: (-4 + x)(9 + x)(x + 13) = 0 Reorder the terms: (-4 + x)(9 + x)(13 + x) = 0 Multiply (-4 + x) * (9 + x) (-4(9 + x) + x(9 + x))(13 + x) = 0 ((9 * -4 + x * -4) + x(9 + x))(13 + x) = 0 ((-36 + -4x) + x(9 + x))(13 + x) = 0 (-36 + -4x + (9 * x + x * x))(13 + x) = 0 (-36 + -4x + (9x + x2))(13 + x) = 0 Combine like terms: -4x + 9x = 5x (-36 + 5x + x2)(13 + x) = 0 Multiply (-36 + 5x + x2) * (13 + x) (-36(13 + x) + 5x * (13 + x) + x2(13 + x)) = 0 ((13 * -36 + x * -36) + 5x * (13 + x) + x2(13 + x)) = 0 ((-468 + -36x) + 5x * (13 + x) + x2(13 + x)) = 0 (-468 + -36x + (13 * 5x + x * 5x) + x2(13 + x)) = 0 (-468 + -36x + (65x + 5x2) + x2(13 + x)) = 0 (-468 + -36x + 65x + 5x2 + (13 * x2 + x * x2)) = 0 (-468 + -36x + 65x + 5x2 + (13x2 + x3)) = 0 Combine like terms: -36x + 65x = 29x (-468 + 29x + 5x2 + 13x2 + x3) = 0 Combine like terms: 5x2 + 13x2 = 18x2 (-468 + 29x + 18x2 + x3) = 0 Solving -468 + 29x + 18x2 + x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 1+3=2+2 | | 0=0.5x^2+3x-2 | | 3(5x+1)+35=9x+2 | | 12847149174817491149728414= | | (3x+6)14=18(3x) | | X-1=1X-4 | | 2x+11=5x+10 | | 6(x-4)=3x-6 | | 4Log(5x-6)=-0.8 | | x+(x+5)+(3x+25)=180 | | 3-6(-2+5-3)= | | 3x+7x=27 | | 6x+8y=500 | | 5x+8x=60 | | x+(x+5)+(3x+25)= | | 3x+4y=24+2x | | x-11=9-x | | 2(5x-x)=59 | | 6=3w | | 5=a+a+-4 | | 5x+15=6x-20 | | 4y-11=37 | | 3y=7-4x | | (6x^3y^4)(5x^5y^4z)= | | 3x-6=156 | | 3x+4y-2y=24+2x | | 3x^4+-1x^3+-22x^2+24x=0 | | .15*y=44.39 | | 12+x+5x=7x | | sinx=0.5x | | -0.01x^2+1.8x-90=0 | | 32.9=3.14*r^2 |